Tinjauan Hukum Islam Tentang Sholat Jamak dan Qadha Bagi Pengantin Ketika Resepsi Pernikahan (Walimah Al-‘Urs) - Faridatul Isnaeni (Universitas Islam Malang, 2022)
One of the Shari'ah taught by Allah SWT to humans is to revive His earth. Allah gave reason as a tool so that humans can develop and improve the functions and benefits of various other creations including plants. Indonesia's potential as one of the world's food reserves should be an opportunity for its people to innovate to create new breakthroughs, especially in the agricultural sector so that its role as one of the world's food centers can be increased. The development of genetic engineering of food crops is one of the clear evidences of success in innovating in agriculture. The great benefits resulting from genetic engineering should continue to be developed into new variants as a source of primary needs. In Islam, looking at a problem tends to be beneficial or harmful. Therefore, currently the problem is only in public awareness so that they have the will to develop and increase innovation in the food sector